Microbiomics and metabolomics explored the characteristics of gut microbiota and metabolites in patients with aortic dissection - Liu, Wenkun; Lin, Qiu; Zhong, Huiying; Liang, Jing; Liu, Binmei; Hu, Yunnan (Frontiers in Cellular and Infection Microbiology, 2025)
Aortic dissection (AD) is a serious and frequently fatal condition with highly variable presentations, which increases the difficulty of diagnosis during the incubation period. The objective of this study was to reveal the influence of gut microbiota and metabolites on the occurrence and development of AD. In the present study, a total of 132 volunteers were recruited, but only 50 met the experimental requirements (including 25 health controls and 25 patients with AD). Patients with AD showed the high levels of systolic blood pressure (SBP) and diastolic blood pressure (DBP), accompanied with aortic dilation. High-throughput sequencing revealed a reduction in the abundance of beneficial bacteria (containing Bifidobacterium and [Eubacterium]_eligens_group) and an increase in harmful bacteria (containing Desulfovibrio and Hungatella) in patients with AD. In addition, untargeted metabolomic identified a total of 304 metabolites that were remarkably changes in AD patients, which major involved in alactose metabolism, caffeine metabolism, tyrosine metabolism, taurine and hypotaurine metabolism, ascorbate and aldarate metabolism, and butanoate metabolism. The above data elucidate that distinct gut microbiota and metabolites in AD patients, offering reliable information to building the prediction models of AD.